2017
DOI: 10.5430/jnep.v7n12p114
|View full text |Cite
|
Sign up to set email alerts
|

Three-year assessment of one pre-licensure cohort of baccalaureate nursing students’ attitude, comfort and knowledge of genomics

Abstract: Objective: Descriptive three-year comparison of one pre-licensure cohort of baccalaureate nursing students' genomic knowledge, attitude and comfort level. Methods: Two analyses were of interest, utilizing the same survey instrument, Genetics/Genomics Literacy Assessment (GGLA): 1) Comparison of pre vs. post intervention on the sophomore (2nd year) class and 2) Retention of the information through junior (3rd year) and senior year (4th year). Two analyses were of interest: 1) Comparison of pre-class vs. post-cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Continued investigation into actual, perceived and retained genomic knowledge amidst pre-licensure students, their confidence and comfort with championing genetically-based healthcare and their perception and attitude about its integration in nursing curricula is required. [42][43][44] Limitations As this was a purposeful sampling with limited participant involved in only one SON, generalizability cannot be achieved in other schools. In addition, the omittance of demographic data for one specific group is a significant limitation.…”
Section: Discussionmentioning
confidence: 99%
“…Continued investigation into actual, perceived and retained genomic knowledge amidst pre-licensure students, their confidence and comfort with championing genetically-based healthcare and their perception and attitude about its integration in nursing curricula is required. [42][43][44] Limitations As this was a purposeful sampling with limited participant involved in only one SON, generalizability cannot be achieved in other schools. In addition, the omittance of demographic data for one specific group is a significant limitation.…”
Section: Discussionmentioning
confidence: 99%
“…The validity and reliability of both GGC and GGLA surveys have effectively proven to provide data on self-perceived knowledge genomics concepts. [1,4,30] 3.1.2 Perceptions and attitudes about genomics integration into nursing practice survey This survey, as Shown in Table 2, comprised seven questions using a 5-point Likert scale of strongly agree/agree, disagree/strongly disagree to unsure for perceptions and attitudes. Perception and attitude survey explored the importance of genomics for the nurse; importance of preparing nurses to utilize genomics; importance of teaching nurses genomics to keep nursing integral in patient/family care; does family history assessment has little value; work environment motivation; interest in taking a genomics course and importance of nurses to advocate for their patients regarding genomic healthcare issues.…”
Section: Methodsmentioning
confidence: 99%
“…[15] Self-rated studies of genetic knowledge in pre-licensure undergraduate or graduate nursing programs further demonstrates an inconsistency in genomic familiarity. [1][2][3][17][18][19][20] Overall, there is a critical lack of genomic understanding, skill and confidence. [21] Studies also confirmed that students felt that nurse educators need more confidence in teaching and explaining this content and faculty need to be adequately prepared to actually inform the future professional.…”
Section: Genomicsmentioning
confidence: 99%
See 2 more Smart Citations